Differentiation of Lactobacillus-probiotic strains by visual comparison of random amplified polymorphic DNA (RAPD) profiles - Abdul Manan, Norlida; Sieo, Chin Chin; Abdullah, Norhani; Ho, Yin Wan (Academic Journals, 2009)
In the present study, distinctive RAPD fingerprints were generated for 12 Lactobacillus-probiotic strains from 5 Lactobacillus species (L. brevis, L. reuteri, L. gallinarium, L. salivarius and L. panis) after optimization of the RAPD parameters such as MgCl2, Taq polymerase, primer concentration and type of primer. The strains were differentiated under the same PCR protocol but different concentration of primer OPM-05 (50 pmole to differentiate the 5 L. brevis strains and 75 pmole to differentiate 2 strains of L. gallinarium, 3 strains of L. reuteri, a strain of L. panis and L. salivarius). The RAPD fingerprints generated could be differentiated by visual comparison of the profiles, without being analysed by relevant software. This allows specific, rapid, immediate and convenient identification of the Lactobacillus strains.